MORPHOBIOCHEMICAL PARAMETERS OF RATS INTRODUCED TO TITANIUM DIOXIDE (experimental study) (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2024)
Due to the widespread use of titanium dioxide nanoparticles (NPsTiO2) in completely different areas of human activity, the question arises about the safety of this nanomaterial. Of particular interest is the study of the problem of the influence of nanoparticles on the body, since the substance in nanoform has completely new properties. The toxic properties of TiO2 NPs have not yet been sufficiently studied, so this topic is relevant. The study assessed the morphological and biochemical parameters of the blood of Wistar rats after intraperitoneal injection of titanium dioxide nanoparticles (TiO2 NPs) at doses of 13.3 and 133.3 mg/kg. The selected concentrations of nanoparticles did not exceed the maximum tolerated dose (MTD) for a given metal. The size of the nanoparticles used was 90 nm. On the first, seventh and fourteenth days, blood was taken from the tail vein for further analysis. The results showed an increase in serum levels of aspartate aminotransferase, alanine aminotransferase, urea and creatinine activity against the background of general leukocytosis. During the experiment, the dose-dependent nature of the effects was not established, but their manifest manifestations were noted on the first day of the experiment, followed by leveling off by the seventh day, which indicates the presence of adaptive reactions in the body. The identified toxic effects of TiO2 NPs indicate a potential risk to women's health.